A stakeholder analysis of divergent supply-chain trends for the European onshore and offshore wind installations. (May 2015) - Wüstemeyer, Christoph; Madlener, Reinhard; Bunn, Derek W.
Abstract: This paper provides a survey-based analysis of investment decisions and structural shifts related to onshore and offshore wind power supply chains. Insights on cost reductions are obtained from a detailed stakeholder survey conducted amongst the European wind power industry in 2012. Overall, a rather more optimistic view of the scope for cost reductions in offshore technology is presented than has previously been evident in empirical analysis. From the analysis we conclude that the wind power industry has experienced a decoupling process of the offshore supply chain from its onshore counterpart with diverging technological requirements. For policy-makers, it is essential to acknowledge that barriers to adoption and the consequent needs for subsidies among the players in the onshore and offshore supply chains seem to differ, and that a micro-level analysis of the innovations and risks involved at the various stages in the supply chain is necessary. Highlights: Survey-based analysis of supply chain trends in the European wind energy industry. Study of technology adoption decisions, structural shifts, and cost projections. Results reveal a decoupling process between onshore and offshore supply chains. Possibilities to transfer knowledge from the onshore to the offshore product vary. The divergent barriers to adoption need to be accounted for by policy-makers.